Maintenance effects of a gamification intervention on motivation and physical activity in patients with coronary heart disease: intermediate results of a randomized controlled trial. (3rd October 2022) - Xu, L; Yu, T; Gao, R; Zhang, X; Pang, Y; Yu, T; Lian, X; Scherrenberg, M; Falter, M; Kaihara, T; Kindermans, H; Coninx, K; et al.
Abstract: Background: Despite the benefits of cardiac rehabilitation and secondary prevention, patients with coronary heart disease frequently fail to meet their daily physical activity goals. When one is stuck in a cycle of bad habits, changing one's behavior can be very challenging. One of the difficulties to maintaining a healthy lifestyle may be a lack of motivation. The use of game design elements (such as points, leaderboards, progress bars, and badges) in non-game contexts to promote motivation and engagement is known as gamification. It could be a powerful tool for encouraging patients to engage in physical activity. However, solid ideas that utilize the fundamental experience and psychological impacts of gaming mechanics must be built upon. Purpose: The aim of this study is to look into the impact of a smartphone-based gamification intervention on physical activity engagement and other related psychological outcomes in patients with coronary heart disease, as well as the 24-week maintenance of effects beyond the 12-week intervention. Methods: Participants with coronary heart disease were randomly assigned to three groups (control group, individual group and team group). The individual and team groups received gamified behavior intervention based on behavioral economic principles. Based on the Individual group, the team earned social incentives (collaboration). The intervention lasted 12 weeks, with another 12 weeks of follow-up. The primary outcomes included the change in daily steps and the proportion of patient-days that step goals achieved. The secondary outcomes included competence, autonomous, relatedness and autonomous motivation. Results: The follow-up period has now been completed by 65 participants (mean age 52.8+10.3, 18.2% female) completed the follow-up period. Compared with the control group (n=17), participants in the individual group (n=25) had a significantly greater increase in mean daily steps from baseline during the intervention group (difference 956; 95% CI, 243–1623; P<0.01), and had a significantly greater proportion of patient-days that step goals achieved (difference 0.35; 95% CI, 0.03–0.12; P<0.001), competence (difference 0.5, 95% CI, 0.3–0.7; P<0.001), autonomous motivation (difference 3.2; 95% CI, 2.0–4.0; P<0.001). However, no significant difference of change in step counts was found between team group (n=23) and control group. During the follow-up period, mean daily steps and autonomous motivation in the individual declined but remained significantly greater than that in the control arm compared with baseline (steps: difference 452; 95% CI, 138–818; P<0.05) (motivation: difference 1.2; 95% CI, 0.3–1.8; P<0.05). Conclusions: A smartphone-based gamification intervention was found to be an effective strategy to enhance motivation and physical activity engagement, as well as having a great maintenance effect. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work is financially supported by a Construction Programme of Independent Innovation Ability of Community Health Nursing Engineering Laboratory in Jilin Province (Study code: 2020C038-8) awarded to FL.